The Dietary Inflammatory Index (DII) and COPD: A Cross-Sectional Study from the NHANES - Luo ZJ; Yang H; Wang Y (International Journal of COPD, 2025)
Zhi Jian Luo, Haiying Yang, Yuan Wang Department of Respiratory and Critical Care Medicine, The Second People’s Hospital of Meishan City, Meishan, Sichuan, 620500, People’s Republic of ChinaCorrespondence: Yuan Wang, Department of Respiratory and Critical Care Medicine, The Second People’s Hospital of Meishan City, Meishan, Sichuan, 620500, People’s Republic of China, Email 2693855887@qq.comBackground: While diet may impact the risk of chronic obstructive pulmonary disease (COPD), the relationship between COPD and dietary inflammatory potential remains largely unexplored. This study aimed to evaluate the association between COPD status and the dietary inflammatory index (DII).Methods: Utilizing NHANES data from 2013 to 2018, the study investigated the relationship between Dietary Inflammatory Index (DII) scores, derived from 24-hour dietary recall interviews, and COPD status. Weighted logistic regression and restricted cubic spline (RCS) analyses were employed to assess this association. Additionally, stratified and interaction analyses were conducted to evaluate the consistency of the relationship and identify potential modifiers.Results: Individuals diagnosed with COPD demonstrated significantly elevated DII scores in comparison to those without COPD. An increment of one unit in the DII was correlated with an increased risk of developing COPD, as indicated by an odds ratio (OR) of 1.05 (95% CI:1.09, 1.21; P=0.007). Following comprehensive multivariate adjustments, the odds ratio for COPD, when comparing individuals in the highest quartile of DII scores to those in the lowest quartile, was 1.34 (95% CI:1.01, 1.77; P< 0.001). A positive linear association was observed between DII and COPD, although the relationship was nonlinear (P=0.618). Moreover, the association between DII and COPD was consistent across various stratified analyses.Conclusion: The study results imply that consuming a pro-inflammatory diet is connected to a greater chance of developing COPD among US residents. Dietary strategies aimed at reducing inflammation might help in preventing COPD and associated illnesses.Keywords: diet, inflammation, dietary inflammatory index, chronic obstructive pulmonary disease, National Health and Nutrition Examination Survey, NHANES